2010
DOI: 10.1007/978-3-642-15155-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Real-Time Mixed-Criticality Jobs

Abstract: Abstract. Many safety-critical embedded systems are subject to certification requirements; some systems may be required to meet multiple sets of certification requirements, from different certification authorities. Certification requirements in such "mixed-criticality" systems give rise to interesting scheduling problems, that cannot be satisfactorily addressed using techniques from conventional scheduling theory. In this paper, we study a formal model for representing such mixed-criticality workloads. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(100 citation statements)
references
References 3 publications
0
100
0
Order By: Relevance
“…Response-time analysis for fixed-priority scheduling has since been improved by Baruah et al. [4] A number of papers have considered the more restricted problem of scheduling a finite set of mixed-criticality jobs (e.g., [5], [6]). Baruah et al have shown that the problem of deciding whether a given set of jobs is schedulable by an optimal scheduling algorithm is NP-hard in the strong sense [6].…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Response-time analysis for fixed-priority scheduling has since been improved by Baruah et al. [4] A number of papers have considered the more restricted problem of scheduling a finite set of mixed-criticality jobs (e.g., [5], [6]). Baruah et al have shown that the problem of deciding whether a given set of jobs is schedulable by an optimal scheduling algorithm is NP-hard in the strong sense [6].…”
Section: A Related Workmentioning
confidence: 99%
“…[4] A number of papers have considered the more restricted problem of scheduling a finite set of mixed-criticality jobs (e.g., [5], [6]). Baruah et al have shown that the problem of deciding whether a given set of jobs is schedulable by an optimal scheduling algorithm is NP-hard in the strong sense [6]. Work on mixed-criticality scheduling has since been focused on finding scheduling strategies that, while being suboptimal, still work well in practice.…”
Section: A Related Workmentioning
confidence: 99%
“…importance) into a common and shared computing platform [1]- [7]. Therefore, mixed-criticality systems are considered to be the next generation of complex embedded systems [1], [8]- [10]. Hence, they have lately become the subject of vast researches considering improvements in Cyber-Physical Systems (CPS) [8], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on different criticality levels, varying degree of assurance should be provided for mixed-criticality systems [7], [12], [13]. Recently, two different approaches have been considered upon mixed-criticality systems [1]. The obvious one is treating criticality as priority of tasks in scheduling algorithms, hence employing priority-based scheduling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation